Note: Fully integrated 3.2 Gbps quantum random number generator with real-time extraction - Zhang, Xiao-Guang; Nie, You-Qi; Zhou, Hongyi; Liang, Hao; Ma, Xiongfeng; Zhang, Jun; Pan, Jian-Wei (Review of scientific instruments, 2016)
We present a real-time and fully integrated quantum random number generator (QRNG) by measuring laser phase fluctuations. The QRNG scheme based on laser phase fluctuations is featured for its capability of generating ultra-high-speed random numbers. However, the speed bottleneck of a practical QRNG lies on the limited speed of randomness extraction. To close the gap between the fast randomness generation and the slow post-processing, we propose a pipeline extraction algorithm based on Toeplitz matrix hashing and implement it in a high-speed field-programmable gate array. Further, all the QRNG components are integrated into a module, including a compact and actively stabilized interferometer, high-speed data acquisition, and real-time data post-processing and transmission. The final generation rate of the QRNG module with real-time extraction can reach 3.2 Gbps.